The Two Sides of the Representative Coin - Keith Sutherland (Studies in Social Justice, 2011)
In Federalist 10 James Madison drew a functional distinction between “parties” (advocates for factional interests) and “judgment” (decision-making for the public good) and warned of the corrupting effect of combining both functions in a “single body of men.” This paper argues that one way of overcoming “Madisonian corruption” would be by restricting political parties to an advocacy role, reserving the judgment function to an allotted (randomly-selected) microcosm of the whole citizenry, who would determine the outcome of parliamentary debates by secret ballot—a division of labour suggested by James Fishkin’s experiments in deliberative polling. The paper then defends this radical constitutional proposal against Bernard Manin’s (1997) claim that an allotted microcosm could not possibly fulfil the “consent” requirement of Natural Right theory. Not only does the proposal challenge Manin’s thesis, but a 28th Amendment implementing it would finally reconcile the competing visions that have bedevilled representative democracy since the Constitutional Convention of 1787.